The psychological impact of esophageal cancer screening on anxiety and depression in China - Zhu, Juan; Ma, Shanrui; Chen, Ru; Liu, Zhaorui; Liu, Zhengkui; Wei, Wenqiang (Frontiers in Psychiatry, 2022)
Objective: The psychological impact of screening is unclear and has been ignored. This study aimed to evaluate the psychological impact of esophageal cancer (EC) screening on anxiety and depression in China. Methods: A multicenter, population-based study in 5 high-risk regions of EC was conducted from 2019 to 2020. Residents were recruited and undertook endoscopic screening, and then were diagnosed with normal, esophagitis, low‐grade intraepithelial neoplasia (LGIN), high‐grade intraepithelial neoplasia (HGIN) and EC. Subjects who didn’t participate in the screening were referred to as the control group. We surveyed their anxiety and depression levels at baseline, after endoscopy and informed different pathological results, to evaluate the psychological impact of the screening process. Results: A total of 2337 subjects completed all surveyed in the screening process (normal: 355, esophagitis: 1713, LGIN: 213, HGIN: 43 and EC: 13, with 63 controls. The levels of anxiety and depression of screeners were significantly higher than those of controls (P<0.001). The fluctuation of anxiety and depression showed a "V" pattern in the screening process. The prevalence of anxiety symptoms at baseline, after endoscopy and after knowing the pathological results were 5.6%, 0.3% and 3.2%, respectively (P<0.001), and the corresponding prevalence of depression were 3.6%, 0.2% and 2.1%, respectively (P<0.001). With the aggravation of pathological results, the levels of anxiety and depression increased significantly (P<0.001), especially in patients informed of HGIN (16.3% and 9.3%) and EC (23.1% and 30.8%). Conclusions: Participation in endoscopic screening may bring short-term adverse psychological effects, especially at baseline and knowing the pathological results. More attention should be paid to participants waiting for endoscopic screening. And the way of informing the screening results of HGIN and EC should be improved. Further precise screening is needed for concentrating on high-risk groups to reduce the psychological impact of screening.